2011
DOI: 10.4315/0362-028x.jfp-10-511
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Novel Multiplex Real-Time PCR Assay for Vibrio Pathogen Detection

Abstract: Three species--Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus--account for the majority of vibrio infections in humans. Rapid and accurate identification of Vibrio species has been problematic because phenotypic characteristics are variable within species. Additionally, biochemical identification and confirmation require 2 or more days to complete. Rapid and sensitive molecular techniques for the detection of vibrio pathogens would be useful for the surveillance and management of outbreaks. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…These methods have high sensitivity, specificity, and speed. The methods used for V. cholerae detection by conventional PCR and/or real-time PCR are well established (Wang et al, 2007;Tebbs et al, 2011;Teklehaimanot et al, 2014). Many research studies have identified Vibrio cholerae strains using 16S rRNA sequencing, pulsed-field gel electrophoresis (PFGE), nested and multiplex PCR (Chakraborty et al, 1999;Kong et al, 2002;Tarr et al, 2007;Mendes et al, 2008;Keshav et al, 2010).…”
Section: Molecular-based Methodsmentioning
confidence: 99%
“…These methods have high sensitivity, specificity, and speed. The methods used for V. cholerae detection by conventional PCR and/or real-time PCR are well established (Wang et al, 2007;Tebbs et al, 2011;Teklehaimanot et al, 2014). Many research studies have identified Vibrio cholerae strains using 16S rRNA sequencing, pulsed-field gel electrophoresis (PFGE), nested and multiplex PCR (Chakraborty et al, 1999;Kong et al, 2002;Tarr et al, 2007;Mendes et al, 2008;Keshav et al, 2010).…”
Section: Molecular-based Methodsmentioning
confidence: 99%
“…The goal of the current study was to develop and evaluate a multiplex real‐time PCR assay that would provide a rapid, sensitive, and quantitative method for the detection of V. anguillarum , V. parahaemolyticus , V. vulnificus , and total bacteria in fish fillets and seawater. While there exist methods to detect V. cholerae, V. parahaemolyticus , and V. vulnificus using multiplex real‐time PCR, there are no methods to detect V. anguillarum and the other Vibrio spp. at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, multiplex qPCR assays have been developed for the detection of Salmonella spp., Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, Campylobacter spp., or Vibrio spp. in various foods (Hong et al 2007;Tebbs et al 2011;Forghani et al 2016;Liu et al 2017;Heymans et al 2018;Parichehr et al 2019). In addition, several applications deal with probiotic or beneficial organisms, such as yeasts, Acetobacter spp., or different lactic acid bacteria (LAB) in kefir or starter cultures in cheese production (Bottari et al 2013;Nejati et al 2020).…”
Section: Discussionmentioning
confidence: 99%